From recession to fragile recovery: an analysis of economic policy (2015-2018) - Corsi, Francisco Luiz (Universidade Estadual Paulista / UNESP, 2020)
This article discusses economic policy in the period between 2015 and 2018 from a critical perspective. We discussed the causes of the strong recession of 2015 and 2016, attributing to neoliberal policy a great responsibility in triggering and deepening the crisis. We also address the fragile resumption of 2017-2018. We seek to critique the proposition that the central problem of the economy would be the fiscal crisis, indicating that the fiscal crisis stems largely from the high interest rate policy advocated by financial capital. We also point out that the Brazilian economy has to be analyzed in the context of the crisis of global capitalism.